PENGELOLAAN BUDIDAYA STROBERI DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI KAMPUNG APENAS - Difinubun, Muhamad Fagi; Tambunan, Ayu Anggraini (LPP ARROSYIDIN, 2024)
Strawberries are a popular fruit commodity among the public. This fruit is a sub-tropical fruit, where its cultivation is the result of the introduction and crossing of several types of potential local varieties. Processing of this fruit is very easy, for example made into syrup, jam or other food mixtures. This fruit is very high in vitamin C content and can help slow down the oxidation process in the human body. Based on its type, this plant can grow well in the highlands with a temperature of 17-20 °C. apenas village located in the jayawijaya mountains can be one of the areas that is quite potential for the cultivation of this type of plant. Where the people of this village are farmers. Strawberry cultivation that is done properly will produce healthy and abundant fruit, so it is possible that it can become a field for the community to increase their income. For this reason, counseling with strawberry cultivation methods is carried out which is expected to provide a brief overview for farmers who do not fully understand strawberry cultivation.